Impact exercises especially on different floors in the development of motor response speed and skill of the reception of the volleyball players - Meshaal , Amer (Journal of Physical Education, 2011)
Extract of the study: The problem lies in the lack of the use of exercise for the clay, which makes performance of the players is not effective for not practicing on such land, and aims Aldrashaly identify the effect of exercise on the clay and hard courts in the development of rapid response and motor fitness and skill of receiving the ball flight, and the hypothesis that exercise of the clay and hardcourt statistically significant variables search tests tribal and dimensional, and adopted the experimental method to study design groups Altgeraatin first (hard court) and group II (clay) and a sample of (10) players, the field procedures were conducted pre-testing on Saturday, 1/9/2011 at 04:30 on the sandy ground outside the stadium and the hall's internal Anbar club volleyball, special exercises were carried out over nine weeks at the rate of three units per week, and post-test was conducted on Thursday, 12/11 / 2011 and on the same pitch and similar circumstances, to conduct pre-testing, to conclude that the use of clay develops the variables of research and the use of exercise training on hardcourt develop agility and skill of the reception and not to develop a variable speed of response kinetics players, volleyball, and recommends that the researcher is certainly on the use of exercise especially on clay for the development of motor response speed, agility and skill with the ball reception plane .